2021
DOI: 10.1021/acsami.1c15174
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Fluoride and Carbonate Lead to Cell Failure in Potassium-Ion Batteries

Abstract: While Li-ion is the prevailing commercial battery chemistry, the development of batteries that use earth-abundant alkali metals (e.g., Na and K) alleviates reliance on Li with potentially cheaper technologies. Electrolyte engineering has been a major thrust of Li-ion battery (LIB) research, and it is unclear if the same electrolyte design principles apply to K-ion batteries (KIBs). Fluoroethylene carbonate (FEC) is a well-known additive used in Li-ion electrolytes because the products of its sacrificial decomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 64 publications
(129 reference statements)
1
16
0
Order By: Relevance
“…For the K + ‐SEI, the area under the F 1s peak decreased relative to the C 1s area, which indicated more extensive hydrocarbon/organic species content during build‐up of the SEI [51] . This agrees with previous reports suggesting differences in the degradation mechanism of the K + electrolytes compared with Li + and Na + [52] …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…For the K + ‐SEI, the area under the F 1s peak decreased relative to the C 1s area, which indicated more extensive hydrocarbon/organic species content during build‐up of the SEI [51] . This agrees with previous reports suggesting differences in the degradation mechanism of the K + electrolytes compared with Li + and Na + [52] …”
Section: Resultssupporting
confidence: 91%
“…[51] This agrees with previous reports suggesting differences in the degradation mechanism of the K + electrolytes compared with Li + and Na + . [52] Looking closer at the F 1s peaks, [53,54] in Figures 5b,c, and in the valence band spectra (Figure S20), the Li + -SEI was dominated by LiF at both formation potentials. For the K + -SEI, the KF peak remained overshadowed by PÀ F containing species (likely arising from KPF 6 crystals as shown in Figure S21 and S22), suggesting poorer incorporation of K + in the SEI structure (also evident from decreasing K 2p peak intensities relative to the graphite CÀ C peak, Figure S19c, d).…”
Section: Resultsmentioning
confidence: 91%
“…ROCO 2 Na, ROSO 2 Na, and RSO 3 Na); this approach can reduce the irreversible decomposition of solvents. 148 However, FEC as the additive in the electrolyte solution of 0.8 M KPF 6 - or 0.8 M KFSI-PC/EC for a HC electrode resulted in a dramatic drop in capacity, whereas capacity remained high for those without FEC addition, 137 as shown in Fig. 6(d).…”
Section: Fec Additive For Different Electrodesmentioning
confidence: 93%
“…In contrast, only a few studies demonstrated the improved SEI properties of K metal in PIBs by electrolyte additives. Although the (de)­intercalation mechanisms of the graphite anode in LIBs and PIBs are similar, one cannot simply apply the knowledge of electrolyte additives obtained from LIBs to PIBs. For example, both potassium fluoride and potassium carbonate are recently demonstrated to be harmful to K + conduction in the SEI . Therefore, the frequently used LIB additives such as fluoroethylene carbonate) and vinylene carbonate) cannot be used in PIBs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, both potassium fluoride and potassium carbonate are recently demonstrated to be harmful to K + conduction in the SEI. 21 Therefore, the frequently used LIB additives such as fluoroethylene carbonate) and vinylene carbonate) cannot be used in PIBs. To avoid the overproduction of KF in SEI, the PIB electrolyte additive must be turned into sulfur, nitrogen, and boron-containing compounds.…”
Section: Introductionmentioning
confidence: 99%